Factors associated with Brugian lymphatic filariasis infection in Terengganu, 2010-2019 - Berahim, Ahmad Syaify (2021)
Background: Lymphatic filariasis is a neglected mosquito-borne tropical disease which is caused by nematodes Wuchereria bancrofti, Brugia malayi or Brugia timori with Brugia malayi as the main species in Terengganu. Lymphatic filariasis cause severe morbidity rather than mortality which can influence other social determinants of health. Terengganu had undergone mass drug administration (MDA) from year 2004 until year 2008 and has passed all three transmission assessment surveys (TAS). Nevertheless, sporadic cases were still reported through active surveillance of night blood survey. Objectives: The main objectives of this study were to determine the associated factors of registered Brugia malayi infection from year 2010 until 2019 in Terengganu state and to describe its proportion and distribution. Methodology: This study was a case-control study and it utilized secondary data from eVekpro online, Terengganu State Health Department, Malaysia Meteorology Department and Entomology Unit, Terengganu State Health Department databases. Simple random sampling applied to the samples which fit to the assigned criteria. The categorical data were described using frequency and proportion while mean and standard deviation for numerical data. Data were analysed using Multiple Logistic Regression to look for associations. Result: The prevalence of filariasis infection from this study was 33.7 per 1,000,000 populations in year 2010 and decrease to 5.6 per 1,000,000 population in year 2019. The data which were analysed using Multiple Logistic Regression found associations of age ≥ 40 years old (AOR:0.395, 95%CI: 0.209, 0.747), mean monthly rainfall (mm) (AOR: 1.003, 95%CI: 1.000, 1.005), mean monthly humidity (%) (AOR: 0.846, 95%CI: 0.745, 0.961), vector density (%) (AOR: 1.030, 95%CI: 1.012, 1.048) and presence of Mansonia vector (AOR: 0.083, 95%CI: 0.034, 0.205) with the occurrence of filariasis infection. Conclusion: The associated factors of filariasis infection in Terengganu state from year 2010 until year 2019 (after Mass Drug Administration) were age, mean monthly rainfall (mm), mean humidity (%), vector density (%) and Mansonia species. The proportion of filariasis infection in Terengganu eleven years post MDA was still lower than one percent as being targeted for filariasis elimination. More local studies on filariasis vectors are needed to ensure that vectors in endemic localities as well as localities identified as at risk do not contain filariasis worms. Young age group should be given special attention during screening and health promotion program as they were more prone to infection due to their activities during active biting time of the vectors. Change of weather should alert the district health officer of possibilities of increase in filariasis infection detection during screening program whereas the data input from entomology study should be analysed accordingly. Although this study found no significant association between non-endemic localities with sporadic case occurrence, localities adjacent to endemic localities are recommended to remain special attention because these localities were not involved in the MDA program but their weather and environmental vector factors are similar to endemic localities which have significant association with the occurrence of filariasis cases.